Molecular characterization of circulating tumor cells—from bench to bedside. (March 2018) - Li, Yanmeng; Wu, Shaohan; Bai, Fan
Abstract: Circulating tumor cells (CTCs) are cancer cells discovered in cancer patients' peripheral blood that successfully escape from the primary tumor site and/or metastases, struggle to survive in the bloodstream, and have potential for seeding metastases. Numerous methods have been proposed to capture CTCs. The value of CTCs as a means of understanding cancer metastasis and a major form of 'liquid biopsy' has been widely demonstrated. Recently, single-cell molecular analyses of CTCs have provided profound biological insights into tumor heterogeneity, mechanism of metastasis and tumor evolution. In addition, because CTC analysis is non-invasive, CTCs exhibit great potential as biomarkers for assessment of cancer prognosis and therapy response. In this review, we summarize modern technologies for CTC detection and isolation, single-cell genomic/transcriptomic characterization of CTCs, and prospective clinical applications of CTCs. We expect that, after further technical improvements in methods of detection and sequencing, CTC analyses will shed new light on the mechanisms driving cancer metastasis and benefit many cancer patients.